(2 2/3+4 2/3):3 2/3=
2 2/5 : (4-3 3/5)=
1/4: 2 3/4 +5 : 2 1/2=
5 1/4:(1/2)do potęgi 2 - 2 2/7:1 3/5=
5*(2/7 : 5/74) - 2 1/3=
6 2/9*(5- 4 1/2: 9)=
proszę was o jak najszybszą odpowiedź proszę



Odpowiedź :

Odpowiedź:

(2 2/3 + 4 2/3) : 3 2/3 = 6 4/3 : 11/3 = 22/3 * 3/11 =  2

2 2/5 : (4 - 3 3/5) = 12/5 : 2/5 = 12/5 * 5/2 = 6

1/4 : 2 3/4 +5 : 2 1/2 = 1/4 : 11/4 =1/4 * 4/11 = 1/11

5 1/4 : (1/2)² - 2 2/7 : 1 3/5 = 21/4 : 1/4 - 15/7 : 8/5 = 21/4 * 4 - 15/7 * 5/8 = 21 - 75/56 = 21 - 1 19/56 = 19 37/56

5 * (2/7 : 5/74) - 2 1/3 = 5 * (2/7 * 74/5)  = 5 *  148/35 = 148/7 = 21 1/7

6 2/9 * (5 - 4 1/2 : 9) = 56/9 * (5 - 9/2 * 1/9) = 56/9 * (5 - 1/2) = 56/9 * 4 1/2 =

= 56/9 * 9/2 = 28

Szczegółowe wyjaśnienie: